An innovative approach for determination of air quality health index - Amit Kumar Gorai; Kanchan; Abhishek Upadhyay; Francis Tuluri; Pramila Goyal; Paul B. Tchounwou (Sci. Total Environ., 2015)
Fuzzy-analytical hierarchical process (F-AHP) can be extended to determine fuzzy air quality health index (FAQHI) for deducing health risk associatedwith local air pollution levels, and subjective parameters. The present work aims at determining FAQHI by considering five air pollutant parameters (SO2, NO2, O-3, CO, and PM10) and three subjective parameters (population sensitivity, population density and location sensitivity). Each of the individual pollutants has varying impacts. Hence the combined health effects associated with the pollutants were estimated by aggregating the pollutants with different weights. Global weights for each evaluation alternatives were determined using fuzzy-AHP method. The developed model was applied to determine FAQHI in Howrah City, India from daily-observed concentrations of air pollutants over the three-year period between 2009 and 2011. The FAQHI values obtained through this method in Howrah City range from 1 to 3. Since the permissible value of FAQHI (as calculated for NAAQS) for residential areas is 1.78, higher index values are of public health concern to the exposed individuals. During the period of study, the observed FAQHI values were found to be higher than 1.78 in most of the day in the months of January to March, and October to December. However, the index values were below the recommended limit during rest of the months. In conclusion, FAQHI in Howrah city was above permissible limit in winter months and within acceptable values in summer and rainy months. Diurnal variations of FAQHI showed a similar trend during the three-year period of assessment. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Community health services; Continuing education; India; Knowledge translation; Rehabilitation; Training of trainers